ANALISIS PENGAWASAN GAYA CINA TERHADAP KUALITAS KERJA KARYAWAN PADA CV. ORGANIK AGRO SYSTEM BANDAR LAMPUNG - Irianto Loka (Sekolah Tinggi Ilmu Ekonomi Gentiaras, 2011)
Supervision of Chinese style using the inspiration of management (the art of warSun Tzu) is empty and the content, weak and strong point confirmed that the leader ormanager must actively take the initiative in controlling a situation rather than vice versa.Supervisory task is to find the point of irregularities and violations of law and filedand submitted to the personnel to take decisive action in the form of administrativesanction even to the level of dismissal. Once the importance of the functions and duties of amanager supervisor in the company details of the tasks or operations require a separateline is clear. So that every employee has a level of discipline in running the task, thismeans that the supervision carried out concerning the quality of existing employees underthe leadership.